Islas Implemented in Uzbekistan for the Regulation and Management of the Electric Power Sector - Shakhrukh, Samiev (Research Parks Publishers, 2023)
This scientific article explores the reforms carried out in the electricity sector in the context of globalization and their results, the problems that persist in the network, natural monopoly situations in the process of electricity generation and transmission, problems in the regulation and management of the electric energy sector, and offers and recommendations on ways to eliminate them.